Methodical recommendations of management development of digital marketing based on economics impressions - Tataryntseva (Kurbatova), Yu. L. (Одеський національний політехнічний університет, 2025)
The article offers methodological recommendations for managing the development of digital marketing in an experience economy. Its relevance stems from the need to integrate production and technological innovations and socio-psychological approaches to achieve emotional consumer engagement. The goal is to develop a systematic approach to managing the development of digital marketing through the phased implementation of changes, from identifying needs to evaluating results. Five key stages of development have been identified that ensure the flexibility of management decisions. Development is viewed as purposeful changes in the technological and socio-psychological components of marketing. The areas of transformation are revealed: the introduction of technologies, the use of innovative channels, and understanding audience behavior. The advantage is the focus on creating a long-lasting positive impression. The recommendations are a practical tool for companies in a dynamic digital environment. У статті запропоновано методичні рекомендації щодо управління розвитком цифрового маркетингу в умовах економіки вражень. Актуальність зумовлена необхідністю інтеграції виробничо-технологічних інновацій і соціо-психологічних підходів для досягнення емоційної залученості споживача. Метою є розробка системного підходу до управління розвитком цифрового маркетингу шляхом поетапного впровадження змін від ідентифікації потреб до оцінки результатів. Визначено п'ять ключових етапів розвитку, які забезпечують гнучкість управлінських рішень. Розвиток розглядається як цілеспрямовані зміни у технологічних і соціально-психологічних компонентах маркетингу. Розкрито напрями трансформації: впровадження технологій, використання інноваційних каналів та розуміння поведінки аудиторії. Перевагою є орієнтація на створення довготривалого позитивного враження. Рекомендації є практичним інструментом для компаній у динамічному цифровому середовищі.
Методичні рекомендації щодо управління розвитком цифрового маркетингу на засадах економіки вражень
Keywords: digital marketing; experience economy; integral indicator; decision tree method; performance evaluation; user experience; marketing strategies; цифровий маркетинг; розвиток; економіка вражень; управління; цифрова трансформація; соціо-психологічна складова; технологічні інновації